PA KUA'S MIRROR FUNCTION FOR CHINA ETHNISTS IN KOTAPINANG DISTRICT, LABUHANBATU SELATAN DISTRICT - Tri Rahma Dana; Usman Pelly; Ichwan Azhari (Universitas Suryakancana, 2021)
This study aims to determine the function of the Pa Kua mirror, namely a mirror with an octagonal shape, made of aluminum and silver which is believed to capture good things and ward off bad things that are usually placed outside the building above the entrance by the ethnic Chinese to live their lives, especially during the Covid-19 pandemic, a situation where all economic activities of many people have become paralyzed and even difficult to survive, such as in Kotapinang, South Labuhanbatu Regency. As the purpose of using this Pa Kua mirror is a tradition passed down from generation to generation to be able to protect the buildings they inhabit. The research method used is descriptive qualitative. With the technique of collecting interview data, observation, and study documentation. The results of the analysis found that this mirror has been used for a long time by ethnic Chinese in their home country of China and has become a tradition they believe in banishing bad energies that enter their residence, and are brought by migrating Chinese ethnicities, especially in this Kotapinang sub-district. and used by those who still believe and still preserve the traditions of their ancestors today.